Ulam-Hyers stability Analysis of Caputo fractional order derivative - Ante, J.E.; Akpan, U.D.; Udofia, E.; Sampson, M.I.; Udoaka, O.G.; Udogworen, W.K. (International Journal of Mathematical Analysis and Modelling, 2026)
This study investigates the Ulam-Hyers stability of fractional derivatives for a given fractional-order system. As a theoretical foundation, fundamental definitions of various fractional derivatives are introduced. By applying the Gronwall inequality, sufficient conditions ensuring stability in the sense of Ulam-Hyers are rigorously established. The derived results constitute notable extensions and refinements of existing findings in the literature.